Proof of concept Exploring bismuth telluride, graphite, and polyvinyl alcohol-based electrospun nanofiber as a potential thermoelectric fabric - Ventura, Jimdel T.
Energy from environment or waste heat can be converted to useable electrical energy through thermoelectric (TE) effect. Seebeck effect is a type of TE effect wherein electricity can be automatically generated when a difference in temperature is observed by a TE material or device. Several researchers nowadays are focused on developing smart fabrics with desirable TE properties---high electrical conductivity, high Seebeck coefficient, and low thermal conductivity. One way to achieve this is by the process of electrospinning nanofibers. This research explored the use of bismuth telluride (Bi2Te3), graphite, anf polyvinyl alcohol (PVA) to make ten (10) spinning solutions with varying concentrations. These spinnning solutions were electrospun into nanofibers and tested for their potential TE properties. Bi2Te3 was used for its efficient TE properties, graphite for its good electrical conductivity, and PVA for its low thermal conductivity and biodegradability. The electrospun nanofiber samples were tested for their electrical conductivity and were all found out to be not electrically conductive. Selected samples were further characterized through Field Emission Scanning Electron Microscopy (FESEM). There was no continuous and stable electrical connection throughout the sample swatches which can be explained by the uneven dispersion of Bi2Te3 and graphite particles. Another limitation which prohibited the samples to exhibit electrical conductive properties was the size of the graphite particles which were not in nanoparticle form. Several factors can be considered for further experiments such as increasing the concentration of Bi2Te3 to increase the TE properties, lowering the concentration of PVA to decrease the insulating property, and using graphite nanoparticles as electric conductive fillers. As a pioneer research on nanofibers in the Bachelor of Science in Clothing Technology (BSCT) program, this study could encourage CT students to explore interdisciplinary research collaboration and innovation in developing smart fabrics.